Vibrational spectroscopy applied to the study of archeological ceramic artifacts from Guarani culture in Brazil - Cavalheri, Adriana S. [UNESP]; Balan, Ana M. O. A. [UNESP]; Kuenzli, Ruth [UNESP]; Constantino, Carlos J. L. [UNESP] (Elsevier B.V., 2010)
An archeological artifact can be seen as a chronological element, which helps to determine the age of certain society and to understand the thinking, values and the way of life of this society. Thus, the classification of archeological artifacts is one of the approaches used to study the cultural system of antique societies trying to reconstruct their history. The "Centro de Museologia, Antropologia e Argueologia (CEMAARQ)" of the "Unesp Univ Estadual Paulista" in Presidente Prudente, São Paulo state, Brazil, develops projects within this context (identification and preservation). This is the case of the archeological site named "Lagoa São Paulo-02" discovered in 1993 at the margins of the Parana river in the region of Presidente Epitacio city, São Paulo state, Brazil. This site has ceramic fragments of different shapes and sizes that have a strong influence of traces of the Guarani culture, which is one of the Brazilian native populations. These samples were basically characterized via micro-Raman scattering and Fourier transform infrared absorption (FTIR) spectroscopies. The main objective was to identify the pigments used in the manufacture of the ceramic artifacts and to analyze the composition of the ceramic body to understand how the artifacts were made. Three pigments were found: red, black and white. For the red pigment were identified characteristic bands of hematite, an iron oxide found in the red rocks of the river banks that were eroded by water. The black pigment, probably, is due to the use of vegetal charcoal, which is found in nature as the product of burning organic material such as wood. For the white pigment, the FTIR spectra suggested the use of kaolin, either in the ceramic body or in the proper white pigment, due to the presence of the characteristic bands of the kaolinite. Complementary, the additives applied as anti-plastics were identified as charcoal and quartz, being the latter found in the rocks present in the archeological site. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Raman spectroscopy; Pigments; Archeological artifacts; Guarani